2006
DOI: 10.1111/j.1365-2966.2006.10219.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodic long-term X-ray and radio variability of Cygnus X-1

Abstract: We present a comprehensive analysis of long-term periodic variability of Cyg X-1 using the method of multiharmonic analysis of variance (mhAoV) applied to available monitoring data since 1969, in X-rays from Vela 5B, Ariel 5, Ginga, CGRO and RXTE satellites and in radio from the Ryle and Green Bank telescopes. We confirm a number of previously obtained results, and, for the first time, find an orbital modulation at 15 GHz in the soft state and show the detailed non-sinusoidal shape of that modulation in the ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 72 publications
6
71
0
Order By: Relevance
“…For strictly sinusoidal flux variability with period P, the SF has minima for τ equal to P and its subharmonics (e.g., Lachowicz et al 2006). Thus, an SF allows for quick confirmation of the findings provided by the periodogram techniques.…”
Section: Structure Function Analysismentioning
confidence: 89%
See 3 more Smart Citations
“…For strictly sinusoidal flux variability with period P, the SF has minima for τ equal to P and its subharmonics (e.g., Lachowicz et al 2006). Thus, an SF allows for quick confirmation of the findings provided by the periodogram techniques.…”
Section: Structure Function Analysismentioning
confidence: 89%
“…It can be directly calculated as P 1 = 1 − F(n , n ⊥ /n corr ; Θ AoV /n corr ) where n ⊥ = n − n and n corr defines a number of consecutive observations being correlated (see Sect. 3.1.4 of Lachowicz et al 2006). A direct derivation of P 1 returns the significance of the periodogram peak (centered at the frequency f 0 ) only under the assumption that any modulation detected has a period, P 0 = 1/ f 0 , which is known in advance.…”
Section: Periodogram Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…The existence of the radio modulation supports the idea that radio emission comes from a continuous jet versus discrete ejections. Another type of periodical behaviour is observed in Cygnus X-1 both at X-ray and radio frequencies, a superorbital modulation of ∼140 d Pooley et al 1999), although such a value is rather unstable and it has been recently showed to be doubled (Lachowicz et al 2006;Rico 2008;Zdziarski et al 2011). The superorbital modulation is possibly related to the precession of the disk-jet system , or alternatively to a variable mass accretion rate (Brocksopp et al 2001), and its period possibly varies when an X-ray spectral state change occurs (Rico 2008).…”
Section: Introductionmentioning
confidence: 99%